Fostering The Development of Generation Z Self-Potential as The Main Basis for Pioneering Creative and Innovative Businesses - M, Ansharuddin; Sholihan (TAAWUN, 2025)
This program aims to improve the soft skills, digital literacy, and technological adaptation of participants While the method used is the Participatory Action Research (PAR) method because it is one of the relevant approaches in fostering the development of the potential of Generation Z. (40 students of SMAN 1 Sangakupra Bawean) as the main basis for starting creative and innovative businesses. The results of this program showed an increase in participants’ confidence in starting a business, better managerial skills, and the ability to utilize digital technology to support their business. The implementation of the service with the title “Guidance on the Development of Generation Z Self-Potential as a Foundation in Pioneering Creative and Innovative Businesses” has gone well and achieved the expected goals. This program succeeded in building young people’s awareness of the importance of recognizing and developing their potential as a provision for starting a creative and innovative business. Through a series of activities that included motivation, skills training, discussions, simulations, and mentoring, participants gained an in-depth understanding of basic entrepreneurial strategies. They not only learned to explore creative ideas, but were also invited to design concrete steps in realizing these ideas into sustainable businesses.